Ethnographica Moralia : Experiments in Interpretive Anthropology - Marcus, George E.; Panourgiá, Neni, 1958- (Book collections on Project MUSE., 2008)
Panourgia and Marcus bring together anthropologists working in various parts of the world (Greece, Bali, Taiwan, the United States) with classicists, historians, and scholars in cultural studies. The volume takes into account global realities such as 9/11 and the opening of the Cypriot Green Line and explores the different ways in which Geertz's anthropology has shaped the pedagogy of their disciplines and enabled discussions among them. Focusing on place and time, locations and temporalities, the essays in this volume interrogate the fixity of interpretation and open new spaces of inquiry. The volume addresses a wide audience from the humanities and the social sciences--anyone interested in the development of a new humanism that will relocate the human as a subject of social action.